Me and white supremacy - Saad, Layla F. (Sourcebooks eXplore, 2022)
Provides a guide for young adults to understand the dangers of white supremacy and how to combat racism, and discusses topics like white privilege, white fragility, tone policing, color blindness, racist stereotypes, cultural appropriation, and allyship. Includes reflection questions, a glossary, and additional resources.